Skills on wheels: caregiver perspectives on the design and long-term impact of a pediatric wheelchair Skills training program. - Loeser, Madison L.; Chase, Tony (Disability & Rehabilitation: Assistive Technology, 2025)
Manual wheelchair skills training programs are novel developments, particularly in the United States. As perceived by the caregivers of participants, this study aimed to examine the long-term impact of the Skills on Wheels program on participants' occupational engagement and quality of life at home, at school, and in the community. Secondly, this study investigated the caregivers' perspectives of the program design of Skills on Wheels. This was a qualitative inquiry based upon thematic analyses of semi-structured interviews after participation in a pediatric wheelchair skills training program. The study participants were 9 caregivers whose children participated in this program over the 2021 and 2022 implementation years. Caregivers were given a 10-question semi-structured interview. The five overarching topics included program impact: (i) occupational engagement, (ii) program impact: quality of life factors, (iii) program resources/design, (iv) novelty/importance of program/wheelchair skills training, and (v) desired continued wheelchair skills practice in the future. Results provided tangible feedback to integrate into program design and supported the Skills on Wheels program's positive value as it relates to impact on quality of life and occupational engagement for participants. IMPLICATIONS FOR REHABILITATION: Wheelchair skills training programs are important for children with disabilities to fill in service gaps related to community mobility. When developing community programs in general, it is necessary to gain the understanding of the impact on caregivers of children with disabilities. This paper provides insight into how a pediatric wheelchair skills training program is viewed by the caregivers of participating children. Therapists and researchers can see the caregiver impact of programs or training such as that described in this study.